DESIGN SALES ACCOUNTING INFORMATION SYSTEM IN KINGDOM STREET FOOD CAFE - Rohmah, Lailatul (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2022)
This research is to find out the sales accounting information system in Kingdom Street Food and then designed a sales accounting information system suitable for Kingdom Street Food. Data collection methods consisted of: interviews, observations, and observations. The research method used was qualitative research with a descriptive approach. The results of this study indicate that: (1) Sales accounting information system at Kingdom Street Food still using a manual system (2) The functions involved in the sales accounting information system are frontliner, kitchen , bar, cashier, and accounting. (3) The documents used in the sales accounting information system are sales orders and struck notes. (4) The records used in the sales accounting information system are sales records . (5) Sales accounting information system procedures include recording, processing and presentation of orders next with receipt of payment and recording. (6) System development includes: (a) Database design (b) system model design. .